Analisis Regresi Linier Guna Mengetahui Pengaruh Tingkat Kematian Kecelakaan Lalu Lintas Terhadap Faktor Mabuk - Alex Alfandianto; Cosmas Eko Suharyanto; Fidelis Nikehana Disa Prasasti (Universitas Katolik Musi Charitas, 2021)
The linear regression analysis model of traffic accidents obtained, showing the results close to the number of accident data that occurred in the period of 3 years (2017-2019). The difference between traffic accidents and traffic accident estimates for 3 years. Observations were also observed on the national level of Indonesia. Based on the influence factors, the traffic accident rate can be estimated with linear regression analysis, based on the model made, so that traffic accidents data can be controlled, in order to know the traffic accident level, so it can be calibrated based on the traffic accident data obtained from the data PT Jasa Raharja. After the test, the influence and the difference that affect the traffic accident rate that the death rate due to traffic accident is not influenced by the factor due to drunk that is equal to 6%. Rather, the most dominant factors such as less traffic order by 20%, factors due to drowsiness by 17%, factors due to fatigue of 14%, and factors due to speeding by 11%.